Performance grading of extracted and recovered asphalt cements. (30th October 2018) - Ding, Haibo; Gyasi, Justice; Hesp, Simon A.M.; Marks, Pamela; Nie, Yihua; Somuah, Michael; Tabib, Seyed; Tetteh, Nathaniel; Ubaid, Imad
Highlights: Current pavement designs based on regular BBR grades fail to provide control of cold temperature cracking. It is imperative to test extracted and recovered asphalt cement for specification grading. Extended BBR grades for 3–5 year old pavements showed deficits ranging from 3 °C to 17.3 °C. Extended BBR grades correlate well with limiting phase angle temperatures. Abstract: Binder extracted and recovered from pavement core samples at two different locations from 18 contracts showed small differences within contracts, well within the minor borderline acceptance criteria. Serious discrepancies were found between original tank sampled asphalt binder and material recovered from pavement cores. Regular BBR grades for recovered materials were on average 2.7 °C in deficit, which is considered high for 3–5 years of service. EBBR grades were on average 7.6 °C in deficit (range 3 °C to 17.3 °C). Equilibrium grades, after 72 h of conditioning, correlated well with temperatures where the phase angle reached 30° after minimal conditioning, suggesting that a limit on phase angle may provide a practical quality assurance measure.